Marked skewing of entire T-cell memory compartment occurs only in a minority of CMV-infected individuals and is unrelated to the degree of memory subset skewing among CMV-specific T-cells - Fuhrmann, Stephan; Reus, Bernhard; Frey, Oliver; Pera, Alejandra; Picker, Louis J.; Kern, Florian (Frontiers in Immunology, 2023)
Background: Chronic CMV infection drives the clonal expansion and accumulation of terminally differentiated, dysfunctional CMV-specific T-cells. Also, CMV-infection appears to accelerate the differentiation of non-CMV-specific T-cells, however, the extent of this phenomenon is unclear. Methods: The distribution of CD4 and CD8 T-cells into four memory subsets determined by CD45RA and CCR7 expression was analyzed in 96 CMV-infected (CMV+) and 81 CMV-uninfected (CMV-) older individuals. In CMV+ individuals, the distribution of IFN-g producing CMV-specific T-cells into the same subsets was analyzed following stimulation with 16 different CMV antigens using flowcytometry (intracellular cytokine staining). We used previously published results to extrapolate the relative size of the entire CMV-specific CD4 and CD8 T-cell response from the summated response to selected antigens. The T-cell memory subset distribution across all CMV antigen-induced responses (weighted mean) was then used to calculate memory subset proportions (in % of CD4 or CD8 T-cells) of CMV-specific and non-CMV-specific T-cells. These were compared to the corresponding proportions in CMV-individuals. Results: Only a minority (20-30%) of CMV+ individuals displayed overall proportions of terminally differentiated T-cell memory subsets above an upper outlier boundary defined in CMV-individuals. The calculated proportions of these subsets among non CMV-specific T-cells in CMV+ individuals also exceeded the corresponding proportions in CMV-people, suggesting their differentiation could be CMV-driven. In CMV+ people showing overall subset distributions within the outlier limits, the memory subset distributions of non-CMV-specific T-cells were more like those in CMV-people. Logistic regression revealed that CMV infection, age, and sex all had significant effects on one or more of the non-CMV-specific CD4 or CD8 T-cell memory subsets in CMV+ individuals with CMV infection showing the strongest effect overall. Surprisingly, except for the CD45RA-/CCR7-CD4 T-cell subset, we only found weak correlations between corresponding memory subset proportions among all T-cells and CMV-specific T-cells. Conclusions: Our analysis supports an effect of CMV infection on non-CMV-specific T-cells, however, limited to a minority of individuals and not closely related to the degree of memory subset differentiation of CMV-specific T-cells. We propose that unknown predisposing factors might determine to what extent CMV infection affects non-CMV-specific T-cell differentiation.